Periarticular and generalised bone loss in patients with early rheumatoid arthritis: influence of alendronate and intra-articular glucocorticoid treatment. Post hoc analyses from the CIMESTRA trial. Issue 6 (9th May 2013) - Jensen, T W; Hansen, M S; Hørslev-Petersen, K; Hyldstrup, L; Abrahamsen, B; Langdahl, B; Zerahn, B; Pødenphant, J; Stengaard-Petersen, K; Junker, P; Østergaard, M; Lottenburger, T; et al.
Abstract : Objectives: The aims of this study were to investigate the influence of alendronate and intra-articular betamethasone treatment on bone mineral density (BMD) changes in hand, lumbar spine and femoral neck during 1 year of a treat-to-target study (Cyclosporine, Methotrexate, Steroid in RA (CIMESTRA)). Patients and methods: A hundred and sixty patients with early, active rheumatoid arthritis (RA) received methotrexate, intra-articular betamethasone and ciclosporin /placebo-ciclosporin. Patients with Z-score ≤0 also started alendronate 10 mg/day. BMD of the hand (digital x-ray radiogrammetry (DXR-BMDhand )), BMD of lumbar spine and femoral neck (dual x-ray absorptiometry (DXA-BMDlumbar spine and DXA-BMDfemoral neck )) and x-rays of hands, wrists and forefeet (modified Sharp-van der Heijde score) were measured at baseline and 1 year, with complete data available in 107 patients. Results: The change in BMD in hand, lumbar spine and femoral neck was negatively associated with the dose of intra-articular betamethasone (p<0.01 for all), but the bone loss in hand was modest and in the axial skeleton comparable with that of healthy individuals. Alendronate did not influence changes in DXR-BMDhand, which averaged −2.8%, whereas significant changes were observed in DXA-BMDlumbar spine and DXA-BMDfemoral neck in alendronate-treated patients (1.8% and 0.8%) compared with untreated patients (–1.8% and –2.2%) (p<0.01 and 0.02). Alendronate did not affect the radiographic progression (alendronate-treated patients: 0 (range 0–19), non-alendronate: 0 (0–18)). Conclusions: In early active RA, intra-articular betamethasone injections added to disease-modifying antirheumatic drug (DMARD) treatment led to minimal loss of hip and lumbar BMD, and the loss could be prevented by treatment with alendronate. Alendronate treatment did not affect radiographic progression.